From "noikokyra' to "lady": Greek immigrant women, assimilation and race - Karpathakis, Anna (The Greek Review of Social Research, 2003)
This paper examines how upward mobility among Greek immigrant women in NYC affects their perceived roles in the family and also the narratives the women construct to frame their experiences. Class and labor market incorporation (formal vs. informal) mainly affect the type of narrative the women construct. Working class women use the ideology of the «noikokyra» to frame their experiences and responsibilities in the home and the community, while lower middle and middle class women select competing elements from American gender and class ideologies to construct their narratives. These two latter groups construct an American-based version of the «lady» as a goal which they aspire to. Despite the differences in gender ideologies between the lower middle and middle class women’s narratives, these two categories of women share the idea of «whiteness» as a goal to be achieved. The paper is based on one-hundred fifteen in-depth interviews with Greek immigrant women in New York between the ages of twenty-two and seventy.